COMPARATIVE ANALYSIS OF THE LEGISLATION OF THE EAEU MEMBER STATES IN THE FIELD OF ORGANIC AGRICULTURE - E. Navasardova; A. Zakharin (Гуманитарные и юридические исследования)
At present, organic agriculture is developing along with the traditional intensive agricultural production. Its purpose is to obtain environmentally friendly products of crop and livestock. In the member states of the Eurasian Economic Union, the process of forming legislation on organic agriculture has just begun. The exception is Armenia, where the law "On organic agriculture" was adopted in 2008. In the Republic of Kazakhstan, the Law "On organic production" has been in force since 2015. The Republic of Belarus and the Russian Federation have adopted relevant laws, but they have not yet entered into force. There is a draft law on organic agricultural production in the Kyrgyz Republic. Agriculture is recognized as a priority in the development of cooperation of the EAEU member states. There will be the adoption of Rules for the circulation of organic products of the Union in the future. In this regard, consideration and comparative analysis of national legislation is relevant. Since most of the EAEU member States have recently adopted relevant laws and have not yet been subjected to a comprehensive analysis, we can also talk about the novelty of the subject of the study. The study has revealed discrepancies in legal approaches associated with different interpretations by national legislators of the concept of organic products, the stages of circulation (production, processing, storage, transportation, and sale). The basis of the legal regime is the requirements for the production of eco-products. Their observance allows in the subsequent time to apply for the corresponding brand (marking). Despite the similarity of the set of functions of public administration, the authors point to a number of differences inherent in both systems of functions and legal regulation of their content. In this regard, the article provides recommendations aimed at unification and harmonization of legal regulation of production of eco-products in the EAEU countries.